The Role of the Intestinal Microbiome in Chronic Psychosocial Stress-Induced Pathologies in Male Mice - Langgartner, Dominik; Vaihinger, Carolyn A.; Haffner-Luntzer, Melanie; Kunze, Julia F.; Weiss, Anna-Lena J.; Foertsch, Sandra; Bergdolt, Stephanie; Ignatius, Anita; Reber, Stefan O. (Frontiers in Behavioral Neuroscience, 2018)
Chronic psychosocial stress is a risk factor for the development of physical and mental disorders accompanied or driven by an activated immune system. Given that chronic stress-induced systemic immune activation is lacking in germ-free and antibiotics-treated mice, a causal role of the gut microbiome in the development of stress-related disorders is likely. To address this hypothesis in the current study we employed the chronic subordinate colony housing (CSC,19 days) paradigm, a pre-clinically validated mouse model for chronic psychosocial stress, known to alter the gut microbial signature and to induce systemic low-grade inflammation, as well as physical and mental abnormalities. In detail, we investigated if i) CSC-induced alterations can be prevented by repeated transplantation of feces (FT) from non-stressed single-housed control (SHC) mice during CSC exposure, and ii) if the transplantation of a “stressed” CSC microbiome is able to induce CSC effects in SHC mice. Therefore, we repeatedly infused SHC and CSC recipient mice rectally with SHC donor feces at days 4 and 11 of the CSC paradigm and assessed anxiety-related behavior on day 19 as well as physiological, immunological and bone parameters on day 20. Furthermore, SHC and CSC recipient mice were infused with CSC donor feces at respective days. To exclude effects of rectal infusions per se, another set of SHC and CSC mice was infused with saline respectively. Our results showed that transplantation of SHC feces had mild stress-protective effects, indicated by an amelioration of CSC-induced thymus atrophy, anxiety, systemic low-grade inflammation and alterations in bone homeostasis. Moreover, transplantation of CSC feces slightly aggravated CSC-induced systemic low-grade inflammation and alterations in bone homeostasis in SHC and/or CSC animals. In conclusion, our data provide evidence for a role of the host’s microbiome in many, but not all, adverse consequences of chronic psychosocial stress. Moreover, our data are consistent with the hypothesis that transplantation of healthy feces might be a useful tool to prevent/treat different adverse outcomes of chronic stress. Finally, our data suggests that stress effects can be transferred to a certain extend via FT, proposing therapeutic approaches using FT to carefully screen fecal donors for their stress/trauma history.